2010
DOI: 10.1103/physreva.81.033803
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency optimization for atomic frequency comb storage

Abstract: We study the efficiency of the Atomic Frequency Comb storage protocol. We show that for a given optical depth, the preparation procedure can be optimize to significantly improve the retrieval. Our prediction is well supported by the experimental implementation of the protocol in a Tm 3+ :YAG crystal. We observe a net gain in efficiency from 10% to 17% by applying the optimized preparation procedure. In the perspective of high bandwidth storage, we investigate the protocol under different magnetic fields. We an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(140 citation statements)
references
References 32 publications
6
134
0
Order By: Relevance
“…Additionally, it has been shown that the shape of each peak is very important to limit this intrinsic dephasing [28]. The highest efficiency for a given optical depth d is obtained for square peaks [29], where the intrinsic dephasing is given by sinc 2 (π/F ). The echo efficiency can then be written as…”
Section: A Afc Echo Delay Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been shown that the shape of each peak is very important to limit this intrinsic dephasing [28]. The highest efficiency for a given optical depth d is obtained for square peaks [29], where the intrinsic dephasing is given by sinc 2 (π/F ). The echo efficiency can then be written as…”
Section: A Afc Echo Delay Memorymentioning
confidence: 99%
“…To create an AFC profile with squarish peaks, one method is to burn each spectral hole one after the other by using sechyp pulses in series [29]. The central frequency of each pulse is then detuned by from the preceding pulse.…”
Section: Shaping Optimization Of the Afcmentioning
confidence: 99%
“…The finesse of the comb used here is 2 as this gives the highest storage efficiency. 18 The experimental setup for creating and characterising the AFCs is shown in Fig. 2 There are three parts to the experiment; repumping, comb creation, and echo measurement.…”
mentioning
confidence: 99%
“…This could lead to the overestimation of the peak width and, consequently, of the theoretical AFC efficiency due to a suboptimal finesse. Note also that higher efficiencies could be reached by tailoring square AFC peaks [44].…”
Section: Memory Characterizationmentioning
confidence: 99%